The Engineering Design Journey : Needs, Concept and Reality : Final Report. - Shallcross, David; Dalvean, Jo; Maynard, Nicoleta (Australian Learning and Teaching Council (ALTC), 2011)
Design is a vital thread of engineering education. It should run throughout an undergraduate program, from first semester, to a major interdisciplinary project in the final semester. Design is often taught by challenging students with a series of un-integrated, open-ended problems that fail to make appropriate links to the bigger picture beyond the individual subject, and certainly beyond the discipline. Sometimes, it is not until their final year that engineering students have the opportunity to integrate their learning across all subjects into a capstone design activity. This is the final report from a project that involves the development of an innovative, interactive learning environment that will allow students to explore the design of several key projects from inception, through construction, to operation. Using spherical photographic images and animations, students will be able to take a virtual tour of a major engineering project following its design, construction and use.